Investigation of the shear strength of HDC deep beams based on a modified direct strut-and-tie model. (30th May 2018) - Deng, Mingke; Ma, Fudong; Ye, Wang; Liang, Xingwen
Highlights: The shear resistance of the fibres is restrained by stirrups. The overestimation to shear resistance of tension rebar is avoided by the µ . The shear resistance of fibres is modified for HDC deep beams. The µ of HDC deep beams is greater than that of RC deep beams. Abstract: Highly ductile fibre reinforced concrete (HDC) is a type of cement-based composite material characterized by tensile strain-hardening behaviour accompanied by the formation of multiple cracks and high compressive strains. The application of HDC in deep beams can significantly enhance the shear strength and improve the shear ductility, both of which are more obvious within deep beams without stirrups. The shear strength of HDC deep beams is obviously not affected by the stirrup ratio, because fibre shear resistance is restrained by stirrups. Two major modifications made to the direct strut-and-tie model (DSTM) are listed below. First, the contribution from the longitudinal main reinforcement is reduced by the strength utilization coefficient for both RC and HDC deep beams. Second, the contribution from the concrete tensile strength is modified for HDC deep beams both with and without stirrups. According to these modifications, the modified direct strut-and-tie model (MDSTM) is proposed for RC and HDC deep beams. The proposed model for RC and HDC deep beams is evaluated using the test results of 201 RC and 28 HDC deep beams, respectively, and the proposed model shows good agreement with the test results.